STEM Teaching and Learning Strategies of High School Parents With Homeschool Students. Issue 5 (June 2018) - Gann, Courtney; Carpenter, Dan
The purpose of this research study was to investigate the teaching and learning strategies used by homeschool parents with high school students. A qualitative case study was used which began with the administration of an open-ended questionnaire to a homeschool community in the southern United States. Twenty-nine parents completed the questionnaire, and 10 of those volunteered to participate in the follow-up procedures, which included interviews, observations, and document collection. Results indicate that parents use a variety of teaching and learning strategies including individualized instruction, mastery learning, self-directed study, collaboration with peers and adults, and application and connection of information.